2011
DOI: 10.1111/j.1574-6941.2011.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of copper on the diversity, abundance and transcription of nitrite and nitrous oxide reductase genes in an urban European estuary

Abstract: In this study, the effects of increasing copper (Cu) concentrations on the denitrification pathway and on the diversity of a denitrifier community and gene expression were evaluated in intertidal sandy sediments of the Douro River estuary (north-west Portugal). The results demonstrated that sediment denitrification rates were highly affected by Cu; almost complete inhibition (85%) of the process was observed in sediments amended with 60 μg Cu g(-1) wet wt sediment. Moreover, the addition of Cu stimulated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 56 publications
5
54
2
Order By: Relevance
“…Numerous studies have examined the factors that influence different pathways involved in denitrification, such as nitrate (Magalhães et al 2005), carbon availability (Henderson et al 2010), pH (Liu et al 2010), and copper concentration (Magalhães et al 2011;Felgate et al 2012). Nevertheless, compaction, as a physical factor, has not received as much attention as the above chemical factors associated with denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the factors that influence different pathways involved in denitrification, such as nitrate (Magalhães et al 2005), carbon availability (Henderson et al 2010), pH (Liu et al 2010), and copper concentration (Magalhães et al 2011;Felgate et al 2012). Nevertheless, compaction, as a physical factor, has not received as much attention as the above chemical factors associated with denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…There are evidences that metals may be an important factor in regulating nitrogen transformations in sediment habitats. For example, in the Douro River estuary (north-west Portugal), the transcription diversity of the nosZ gene showed a drastic decrease with the increase of Cu concentration (Magalhães et al 2011). The metal toxicity was modulated by sediment properties (metal concentrations, grain size, organic carbon to nitrogen ratio, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reduced sulfur compounds might be oxidized to sulfuric acid if sufficient oxygen is introduced by the plants (Stubner et al 1998), thereby a lower pH in the vegetated sediments was observed. Several studies have illustrated that soil or sediment physiochemical properties are a major factor group influencing the activity, size, and community of denitrifiers (Perryman et al 2011;Bañeras et al 2012;Guo et al 2013;Li et al 2013). The changes in the sediment properties caused by these factors play an important role in affecting the denitrifier activities and abundances, thus further shaping the denitrifier community compositions.…”
Section: Discussionmentioning
confidence: 98%